Superoxide dismutase and catalase activities of cultured erythrocytes infected with Plasmodium falciparum. - S. Areekul (2018)
It has already shown that catalase activity is significantly decreased in red cells of patients with P. falciparum. The mechanism suggested was by this enzyme inactivation through increased H2O2 generated during malarial infection. The present study was performed to verify this hypothesis. Catalase activities of red cells with high or low parasitemia in patients with P. falciparum were found to be lower than those of normal red cells. However, P. falciparum-infected red cells cultured for one week showed similar SOD and catalase levels to normal red cells. There was also no significant difference in the catalase levels between the parasitized and non-parasitized red cells. The difference in catalase activity of infected red cells before and after culture could be explained in terms of the activation of mononuclear cells and macrophages in vivo. During the sojourn of the parasitized red cells in close proximity to the macrophages of the spleen, they might trigger oxidative bursts resulting in increased H2O2. In order to protect themselves from oxidant damage, the catalase in the infected red cells could be inactivated by H2O2 resulting in the reduction of this enzyme.